1987
DOI: 10.1302/0301-620x.69b5.3680327
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of adolescent disc herniation

Abstract: Magnetic resonance imaging (MRI) was used to compare the appearance of the spine in 20 adolescents with proven symptomatic intervertebral disc herniations with that in 20 asymptomatic patients who acted as controls. Abnormality in the signal from the nucleus pulposus of one or more discs was present in all patients, while only four of the 20 controls had any abnormal signals. In all the patients the symptomatic disc produced an abnormal signal and in most a herniated fragment of the nucleus pulposus was identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Disc protrusions are not uncommon in asymptomatic adult populations, with prevalences ranging from 10% to 30%, depending on the studied age group. [12][13][14][15][16][17][18][19][20] In general, epidemiologic studies demonstrate that the prevalence of disc protrusions in asymptomatic populations increases with age. [12][13][14][15][16][17][18][19][20] Our study found that nearly 20% of asymptomatic patients 50 years of age or younger had disc protrusion compared with nearly 40% in the symptomatic group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disc protrusions are not uncommon in asymptomatic adult populations, with prevalences ranging from 10% to 30%, depending on the studied age group. [12][13][14][15][16][17][18][19][20] In general, epidemiologic studies demonstrate that the prevalence of disc protrusions in asymptomatic populations increases with age. [12][13][14][15][16][17][18][19][20] Our study found that nearly 20% of asymptomatic patients 50 years of age or younger had disc protrusion compared with nearly 40% in the symptomatic group.…”
Section: Discussionmentioning
confidence: 99%
“…5,13,15,18,19,23,27,29,[32][33][34][35][36] Some studies have demonstrated no association between disc degeneration and low back pain, especially in older individuals. 37,38 Our meta-analysis on 12 studies found a strong association of disc degeneration and low back pain in individuals 50 years of age or younger, with Ͼ30% of asymptomatic individuals and Ͼ50% of symptomatic individuals found to have disc degeneration on MR imaging.…”
mentioning
confidence: 99%
“…Different types of endplate changes (Scheuermann disease, Schmorl nodes) have previously been described in relation to LBP in children and adolescents, 8 and disc herniations have also been found. 9 To identify "abnormalities" in young lumbar spines, it is necessary to define the limits of "normality." This process remains difficult because our knowledge of spinal morphology, development, and degeneration in children and adolescents is rather limited.…”
mentioning
confidence: 99%
“…[11][12][13][14] Magnetic resonance imaging (MRI) studies are useful sources of information regarding lumbar spinal anatomy in humans. However, only 3 cross-sectional case control studies, 9,15,16 and one longitudinal study [17][18][19][20] involving a total of 171 symptomatic individuals and 202 controls involving adolescents are available. These studies show that disc degeneration and herniations are more common in patients with LBP compared to controls, while the frequency of MRI findings of reduced disc height does not differ.…”
mentioning
confidence: 99%
“…The plain radiograph is seldom helpful. MRI study should be interpreted with caution as a high instance of 'abnormalities' is reported in symptomless controls [53] and 'disc degeneration' is found no more frequently in this group than in controls, although disc protrusion is [54]. Although in children a large amount of nucleus pulposus tends to be extruded, sciatica is uncommon.…”
Section: Disc Herniationmentioning
confidence: 86%